2018
DOI: 10.1002/eco.1994
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal coupling of conifer sap flow and vapour pressure deficit across topoclimatic gradients in a subalpine catchment

Abstract: The hydroclimatic controls on transpiration often follow hillslope‐ or catchment‐scale topography in water‐limited ecosystems; however, rates of transpiration may deviate from these patterns due to microtopographic variation in environmental conditions or physiology. Here, we assessed the microtopographic effects on water use of five conifer species within four subcatchments in western Montana along a water availability gradient that was driven by aspect and elevation. To infer physiological processes at both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 117 publications
0
17
0
2
Order By: Relevance
“…While we did not directly examine HR in our study, it was likely that HR did occur, although the degree in which HR influenced soil water and subsequent water source use likely differed between low and high‐elevation trees. At the low‐elevation site, HR was probably less important because the mid‐summer drought can often lead to relatively dry soils (<10% volumetric water content), resulting in decreased mid‐summer transpiration rates (Looker, Martin, Hoylman, Jencso, & Hu, ) or even fine root mortality. Studies have found that HR is more likely to occur if fine roots remain active (Meinzer et al., ; Warren et al., ) and when pulses of moisture are occasionally available (Brooks et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…While we did not directly examine HR in our study, it was likely that HR did occur, although the degree in which HR influenced soil water and subsequent water source use likely differed between low and high‐elevation trees. At the low‐elevation site, HR was probably less important because the mid‐summer drought can often lead to relatively dry soils (<10% volumetric water content), resulting in decreased mid‐summer transpiration rates (Looker, Martin, Hoylman, Jencso, & Hu, ) or even fine root mortality. Studies have found that HR is more likely to occur if fine roots remain active (Meinzer et al., ; Warren et al., ) and when pulses of moisture are occasionally available (Brooks et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…During this period, soil moisture levels were high (Yano et al 2019), soil N supply and availability rates were high (Figs. 9, 10), and transpiration rates were high (Looker et al 2018), enhancing rates of N mass flow to the roots (Lambers et al 1998, Matson et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Karst aquifers are unique because, unlike other aquifers, they are characterized by a threefold permeability: a. matrix porosity due to pore spaces, formed within the rocks by constitutive minerals (sub-millimeter scale); b. secondary or fracture porosity formed by orogenic processes (millimeter scale), and c. tertiary or conduit porosity where cavities and integrated conduits are formed by chemical dissolution, which is a characteristic feature of karst areas [51]. Soil water fluxes in karst areas are therefore very complex [18], and hydrologic fluxes are often estimated by eddy covariance [52][53][54], tree sap flow measurements [55][56][57][58], or simulated by hydrological models [37,48,[59][60][61][62][63][64]. In our study, the Brook90 hydrological model was used to simulate indicators of hydrologic fluxes (drainage flux-DF; canopy interception-I; transpiration-TRAN and soil evaporation-SE) in gaps and forests over a 13-year period.…”
Section: Introductionmentioning
confidence: 99%